Integration of Religious Moderation Values in Contemporary Islamic Religious Education Material - Evi Susanti; Amma Ainun; Rusmaeni Rusmaeni; Ruslan Ruslan; Muslimin Muslimin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the integration of religious moderation values in contemporary Islamic Religious Education (PAI) materials, their implementation in the learning process, and their implications for students’ religious attitudes. The research employed a qualitative approach with a library research design through a systematic analysis of academic sources published between 2022 and 2026, including accredited journal articles, scholarly books, and curriculum documents. Data were collected through documentation techniques and analyzed using thematic analysis supported by NVivo software to ensure systematic and transparent coding procedures. The findings indicate that the integration of religious moderation values is carried out conceptually, substantively, and structurally within PAI materials. The implementation is reflected in explicit lesson planning, dialogical learning strategies, and authentic assessment addressing both cognitive and affective domains. The integration contributes to strengthening tolerance, enhancing national commitment, and fostering proportional religious understanding among students.